3 kV monolithic bidirectional GaN HEMT on sapphire - Md Tahmidul Alam; Swarnav Mukhopadhyay; Md Mobinul Haque; Shubhra S. Pasayat; Chirag Gupta (Applied Physics Express)
3 kV breakdown voltage was demonstrated in monolithic bidirectional Gallium Nitride (GaN) High Electron Mobility Transistors (HEMTs) having potential applications in 1200 V or 1700 V class power converters. The on-resistance of the fabricated transistors was ∼20 Ω.mm (∼11 mΩ.cm ^2 ). The breakdown voltage was optimized with two field plates on either side of the transistor. Shorter first field plate lengths (≤2 μm) resulted in higher breakdown voltage and the possible reason was discussed. The transistors had a steep subthreshold swing of 92 mV dec ^−1 . The fabricated transistor was benchmarked against the state-of-the-art monolithic bidirectional GaN HEMTs in the performance matrices of breakdown voltage—on resistance, that showed crucial progress.